Trunk rotational strength deficits in elite adolescent trampolinists - Stanton, R.; Reaburn, P.; Bryant, A.; Dascombe, B.; Kelso, D.; Mason, J.; Weaver, B. (Australian Conference of Science and Medicine in Sport and Third National Sports Injury Prevention Conference: 2003. Tackling the barriers of performance and participation, 2003)
The compulsory routine in Trampoline sports competition requires the performer to complete 10 skills of which a number require axial rotation of the body. All are completed in the same rotational direction. It was hypothesized that the volume of training and competition may predispose trampolinists to bilateral rotational strength deficits. Thus the purpose of this study is to investigate bilateral rotational strength deficits in elite adolescent trampolinists. Seven elite trampolinists (mean age 15.5 years; range 13 - 20 years) were assessed for isometric trunk rotational strength and peak activation of the external oblique muscles. Data suggests elite adolescent trampolinists display significant bilateral rotational strength deficits without concomitant bilateral deficits in peak activation of the external oblique muscles. It may be suggested that to minimize adverse postural deficits and subsequent lumbar pain, trampolinists engage in contralateral rotational training to encourage strength balance. The effect on performance is unknown.